Spatiotemporal Integration in Somatosensory Perception: Effects of Sensory Saltation on Pointing at Perceived Positions on the Body Surface - Trojan, Jörg; Stolle, Annette M.; Mršić Carl, Antonija; Kleinböhl, Dieter; Tan, Hong Z.; Hölzl, Rupert (Frontiers in Psychology, 2010)
In the past, sensory saltation phenomena (Geldard and Sherrick, 1972) have been used repeatedly to analyze the spatiotemporal integration capacity of somatosensory and other sensory mechanisms by means of their psychophysical characteristic. The core phenomenon consists in a systematic mislocalization of one tactile stimulus (the attractee) toward another successive tactile stimulus (the attractant) presented at another location, increasing with shorter intervals. In a series of four experiments, sensory saltation characteristics were studied at the forearm and the abdomen. Participants reported the perceived positions of attractees, attractants, and reference stimuli by pointing. In general, saltation characteristics compared well to those reported in previous studies, but we were able to gain several new insights regarding this phenomenon: (a) the attractee–attractant interval did not exclusively affect the perceived attractee position, but also the perceived attractant position; (b) saltation characteristics were very similar at different body sites and orientations, but did show differences suggesting anisotropy (direction-dependency) in the underlying integration processes; (c) sensory saltation could be elicited with stimulation patterns crossing the body midline on the abdomen. In addition to the saltation-specific results, our experiments demonstrate that pointing reports of perceived positions on the body surface generally show pronounced systematic biases compared to veridical positions, moderate intraindividual consistency, and a high degree of inter-individual variability. Finally, we address methodological and terminological controversies concerning the sensory saltation paradigm and discuss its possible neurophysiological basis.